2020
DOI: 10.1177/0013124520915597
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Teacher Relations, Parental Self-Efficacy, and Parents’ Help-Seeking From Teachers About Children’s Learning and Socio-Emotional Problems

Abstract: In light of the backdrop of change processes within the education system in recent years, including the enlarging of school boundaries and parents’ increasing involvement in school life, this study aspired to understand how parents perceive parent–teacher relations alongside their self-efficacy as influencing their help-seeking from teachers in two main dimensions: learning and socio-emotional. Using the quantitative method, 192 Israeli parents answered a questionnaire measuring parent–teacher relations, paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Teaching, especially in primary schools in Israel, has long been considered "women's work," that is, a low-paid and low-status occupation (Addi-Raccah, 2002). Moreover, primary school teachers have lower education and income than the parents who participated in this study (see Harpaz & Grinshtain, 2020).…”
Section: Pedagogical Policymentioning
confidence: 94%
“…Teaching, especially in primary schools in Israel, has long been considered "women's work," that is, a low-paid and low-status occupation (Addi-Raccah, 2002). Moreover, primary school teachers have lower education and income than the parents who participated in this study (see Harpaz & Grinshtain, 2020).…”
Section: Pedagogical Policymentioning
confidence: 94%
“…Comprehensive metaanalyses of mindfulness-based interventions implemented in schools have generally had positive results (Carsley, Khoury and Heath, 2018;Zenner, Herrnleben-Kurz and Walach, 2014). At the same time, schools bene t most from systemic approaches in which innovation and change are introduced coherently throughout the school organization and its curricula (Miller et al, 2018;Harpaz and Grinshtain, 2020). Hence when SEL practices are introduced as short-term interventions, rather than through holistic approaches that address the school as a whole, results may be hard to sustain over time (Sheinman et al, 2018;Ergas and Hadar, 2019).…”
Section: Why Flourishing? Why Now?mentioning
confidence: 99%
“…Social support has been proven to have a significant effect on reducing the negative impact of caring for children who have disabilities (Alon, 2019). The social support felt by the mother can be in the form of the mother's belief in the existence of others who can provide empathy, cooperation, and assistance in overcoming parenting challenges (Alon, 2019;Harpaz & Grinshtain, 2020). Signs which contain the meaning of social support are in the form of words.…”
Section: Social Supportmentioning
confidence: 99%
“…According to Bandura, parenting self-efficacy defined as an individual's perception of his ability to successfully carry out his/her parenting role (Wittkowski et al, 2017;Albanese et al, 2019). The characteristics of parents who have a high level of parenting selfefficacy can be seen from the willingness of parents to seek support from the social community to deal with the obstacles experienced by their children (Harpaz & Grinshtain, 2020). Referring to social learning theory, Bandura & Adams revealed that the development of parents' beliefs about their ability to care for children is influenced by experiences of success in parenting practices, parents' observations of the behaviour of others in carrying out parenting tasks, social reinforcement received by parents, for example, encouragement or praise from others, and physiological-emotional conditions experienced by parents, for example, self-confidence, satisfaction, and happiness (Wittkowski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%